2019
DOI: 10.1126/scitranslmed.aat9284
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan synthase 2–mediated hyaluronan production mediates Notch1 activation and liver fibrosis

Abstract: Hyaluronan (HA), a major extracellular matrix glycosaminoglycan, is a biomarker for cirrhosis. However, little is known about the regulatory and downstream mechanisms of HA overproduction in liver fibrosis. Hepatic HA and HA synthase 2 (HAS2) expression was elevated in both human and murine liver fibrosis. HA production and liver fibrosis were reduced in mice lacking HAS2 in hepatic stellate cells (HSCs), whereas mice overexpressing HAS2 had exacerbated liver fibrosis. HAS2 was transcriptionally up-regulated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(132 citation statements)
references
References 52 publications
5
127
0
Order By: Relevance
“…Jagged-1 expressed on liver macrophages and HSCs could interact with Notch1 on HSCs, promoting Notch1-mediated HSC activation and fibrosis. 57 These observations support that the bidirectional regulation between macrophages and HSCs is the key mechanism of fibrosis progression.…”
Section: Crosstalk Of Hscs and Macrophages Is Crucial For Liver Fibromentioning
confidence: 54%
See 2 more Smart Citations
“…Jagged-1 expressed on liver macrophages and HSCs could interact with Notch1 on HSCs, promoting Notch1-mediated HSC activation and fibrosis. 57 These observations support that the bidirectional regulation between macrophages and HSCs is the key mechanism of fibrosis progression.…”
Section: Crosstalk Of Hscs and Macrophages Is Crucial For Liver Fibromentioning
confidence: 54%
“…Activated HSCs overexpress HAS2 that synthesizes HA, and then the overproduced HA promotes HSC activation and fibrosis through CD44/Notch signaling. 57 ECM stiffness also contributes to HSC activation. Compositional changes and crosslinking of collagen fibers by lysyl oxidaselike enzyme (LOXL) contribute to the increased stiffness of fibrosis, which activates HSCs through mechanosensing signaling, including the YAP-activating pathway.…”
Section: The Role Of Hepatic Stellate Cells In Liver Fibrosis and Canmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent extensive study demonstrated that conditional knockout of has2 HSCs reduced liver fibrosis in mice [31]. It also shows that HAS2 was upregulated by transforming growth factor-β through Wilms tumor 1 to promote transdifferentiation of HSCs towards myofibroblasts.…”
Section: Discussionmentioning
confidence: 97%
“…Hepatic stellate cells are a possible source of hyaluronan that could possibly be activated in this specific context. 83 Similarly, liver endothelial cells could actively participate in hyaluronan remodelling and production. 84 Finally, genetic impairment of platelets' ability to release αgranules (in Nbeal2 -/mice) resulted in amelioration of liver damage and inflammation, whereas simple inhibition of platelet aggregation did not reveal any beneficial effect.…”
Section: Platelets In Alcohol-related and Non-alcoholic Steatohepatitismentioning
confidence: 99%